Forced Digital Transformation: Adapting to a New Reality During COVID-19 - Case Studies of Leading Companies' Responses - Benmoussa , Mohammed (Finance and Business Economies Review, 2023)
This extensive research article analysed how COVID-19 has accelerated digital transformation globally across businesses. Technologies like artificial intelligence, cloud computing, 5G networks and IoT have enabled organisational resilience and adaptation throughout the pandemic. Remote work, online delivery models and supply chain digitisation have all been dramatically hastened. While forced by external shock, digital transformation has supported business continuity and recovery during an extraordinarily challenging period. Companies further along in their digital journeys generally exhibited greater agility in the face of massive uncertainty and volatility. Digital capabilities and mindsets will only become more critical as technological change accelerates. COVID-19 pulled future trends forward by years in mere months. Organisations must continue prioritising smart investments in emerging technologies, dynamic workflows, cybersecurity, continuous workforce upskilling and decentralised innovation. By leveraging the pandemic's lessons, companies can build greater resilience to withstand future shocks. Though imposed by crisis, digital transformation can enable organisations to flourish in the next normal.